Курган: могила или святилище? - Берестнев, С. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryS. Berestnev. A Burial Mound: a Grave or a SanctuaryThe article is about the matter of the origin and the purpose of a relief ground construction: a burial mound. On the basis of the architecture analysis of the ancient Eastern Europe South burial mounds, the following conclusion is being made: the burial mounds appear as cattle breeding communities’ religious centers, as the steppe analogue for temples of settled farmers. The burial mounds simultaneous appearance at the Northern Caucasus and the north-west Black Sea littoral may be explained as the front Asia and Balkans-Carpathians regions early-farming civilizations’ influence, which confessed similar religious-mythic doctrines. On the basis of burial mound’s function, as open type sanctuary lays the reason of human sacrifice which permits to obtain reliable contact with supernatural circle. That is why at the inlet graves may be seen the methods of sanctuary’s activation, and their stratigraphic sequence reveal the periods of dominant groups which realized their right to exploit ceremonial centers.